1993
DOI: 10.1287/mnsc.39.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Makespan in the 3-Machine Assembly-Type Flowshop Scheduling Problem

Abstract: This paper considers minimizing the makespan in the 3-machine assembly-type flowshop scheduling problem. After problem formulation, we present a proof to show that the general version of this problem is strongly NP-complete. We then discuss a few polynomially solvable cases of the problem and present the solution algorithms. Next, a branch and bound solution scheme is suggested. Finally, three heuristics to find approximate solutions to the general problem are proposed and their error bounds are analyzed.flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
120
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(121 citation statements)
references
References 17 publications
0
120
0
1
Order By: Relevance
“…The special case where all the jobs have the same processing time on the second-stage machine is polynomially solvable for both the problem (Cheng and Wang, 1998) and the max || 3 C MAF problem (Lee et al, 1993). In this section we shall show that the special case of the later problem…”
Section: Np-hardnessmentioning
confidence: 92%
See 2 more Smart Citations
“…The special case where all the jobs have the same processing time on the second-stage machine is polynomially solvable for both the problem (Cheng and Wang, 1998) and the max || 3 C MAF problem (Lee et al, 1993). In this section we shall show that the special case of the later problem…”
Section: Np-hardnessmentioning
confidence: 92%
“…In the past decades, this seminal work has inspired numerous research endeavors in the scheduling literature (Pinedo 2001, Reisman et al 1997. As a generalization of Johnson's two-machine flowshop, the three-machine assembly flowshop problem motivated by the manufacturing of fire engines was studied by Lee et al (1993). Like the three-machine flowshop problem (Garey et al 1979), the problem to minimize the makespan in an assembly flowshop becomes computationally intractable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pinedo, 2012). When the objective function is the makespan, the problem has been proved to be strongly NP-complete for three or more machines (Lee, Cheng, & Lin, 1993) and for the tardiness objective (Du et al, 2012). A generalization of the FS and parallel-machines environments is the FFS.…”
Section: Introductionmentioning
confidence: 99%
“…For multiple jobs (with each job consisting of one unit of a product), the assembly scheduling problem was first studied by Lee et al, (1993); for the objective of minimising the makespan. Potts et al (1995) have shown that this problem is strongly NP-hard, and have provided a polynomial-time approximation algorithm with a worst-case performance bound.…”
Section: Introductionmentioning
confidence: 99%